The Emotional Expression of Families who have Schizophrenic Clients - Efri Widianti; Annisa Susanti Karmansyah; Desy Indra Yani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Recurrence in schizophrenic clients is still prevalent in every year, especially in the patients who perform home care. When treating patients with schizophrenia, some families feel the burden of treatment that led to high emotional expression. This study purpose to identify the emotional expression of families who have schizophrenic clients in Kersamanah, Garut. The design of study is quantitative descriptive with the number of respondents 69 family members who live with pastients with schizophrenia, using purposive sampling. This study used Family Questionnaire (FQ) with a reliability value of 0.897. Data analysis using descriptive statistics in percentage form. The results showed that 65 (94.2%) respondents had low emotional expression, and 4 (5.8%) respondents had high emotional expression. The dominant aspect possessed by the respondent with high emotional expression in this research is emotional over involvement. The findings of this study depicted that expression of emotions is influenced by several factors, especially by local cultures.